Syngas production by catalytic partial oxidation of methane over (La0.7A0.3)BO3 (A = Ba, Ca, Mg, Sr, and B = Cr or Fe) perovskite oxides for portable fuel cell applications - Khine, M.; Chen, L.; Zhang, S.; Lin, J.; Jiang, San Ping (Elsevier Ltd, 2013)
Hydrogen is a clean energy carrier for the future. More efficient, economic and small-scale syngas production has therefore important implications not only on the future sustainable hydrogen-based economy but also on the distributed energy generation technologies such as fuel cells. In this paper, a new concept for syngas production is presented with the use of redox stable lanthanum chromite and lanthanum ferrite perovskites with A-site doping of Ba, Ca, Mg and Sr as the pure atomic oxygen source for the catalytic partial oxidation of methane. In this process, catalytic partial oxidation reaction of methane occurs with the lattice oxygen of perovskites, forming H2 and CO syngas. The oxygen vacancies due to the release of lattice oxygen ions are regenerated by passing air over the reduced nonstoichiometric perovskites. Studies by XRD, temperature-programmed reduction (TPR) and activity measurements showed the enhanced effects of alkaline element A-site dopants on reaction activity of both LaCrO3 and LaFeO3 oxides. In both series, Sr and Ca doping promotes significantly the activity towards the syngas production most likely due to the significantly increased mobility of the lattice oxygen in perovskite oxide structures. The active oxygen species and performance of the LaACrO3 and LaAFeO3 perovskite oxides with respect to the catalytic partial oxidation of methane are discussed.